2013
DOI: 10.1007/s00213-013-3112-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of serotonin 5-HT3 receptors in the modulation of noradrenergic transmission by serotonin reuptake inhibitors: a microdialysis study in rat brain

Abstract: The SSRI citalopram modulates central noradrenergic neurotransmission by activation, through endogenous serotonin, of 5-HT3 receptors expressed in the somatodendritic (LC) and terminal (PFC) areas, which subsequently promote an enhancement of local NA. Therefore, 5-HT3 receptors and somatodendritic α2-adrenoceptors in the LC play an important role in the global effect of SSRIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Parallel to these experimental results, vortioxetine treatment has been shown to increase noradrenaline levels in the locus coeruleus and dopamine levels in the prefrontal cortex [ 8 ]. In fact, these increases have been associated with the 5HT 3 receptor antagonistic [ 9 ] and 5-HT 1A agonistic effects of this drug [ 10 ]. Indeed, in a study by Micov et al, the antiallodynic activity of vortioxetine in a model of oxaliplatin-induced neuropathy was associated with increased amounts of noradrenaline (along with serotonin) in the brainstem of mice [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel to these experimental results, vortioxetine treatment has been shown to increase noradrenaline levels in the locus coeruleus and dopamine levels in the prefrontal cortex [ 8 ]. In fact, these increases have been associated with the 5HT 3 receptor antagonistic [ 9 ] and 5-HT 1A agonistic effects of this drug [ 10 ]. Indeed, in a study by Micov et al, the antiallodynic activity of vortioxetine in a model of oxaliplatin-induced neuropathy was associated with increased amounts of noradrenaline (along with serotonin) in the brainstem of mice [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It acts as an inhibitor on the serotonin transporter, and also as an agonist (5-HT 1A ), partial agonist (5-HT 1B ) and antagonist (5-HT 1D , 5-HT 3 , 5-HT 7 ) of serotonin receptor subtypes [ 3 , 4 ]. Vortioxetine exerts its pharmacological effects in the central nervous system by regulating the release of various neurotransmitters such as noradrenaline, dopamine, histamine, acetylcholine, glutamate, gamma-aminobutyric acid, as well as serotonin [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…) despite their pronounced effects on enhancing forebrain monoamine availability (Owen and Whitton ; Fernandez‐Pastor et al . ; Kaminska et al . ; Ortega et al .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effect of SSRIs on acetylcholine efflux is of interest as these agents show limited effects in treating cognitive symptoms in major depression (Jeon et al 2014;Keefe et al 2014) despite their pronounced effects on enhancing forebrain monoamine availability (Owen and Whitton 2006;Fernandez-Pastor et al 2013;Kaminska et al 2013;Ortega et al 2013). Clearly, enhancing forebrain monoamine function alone by SSRIs appears to be insufficient to broadly improve cognitive dysfunction in major depression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an acute dose of vortioxetine increased norepinephrine in the nucleus locus coeruleus ( 14 ). It was suggested that this increase was not due to a direct effect of vortioxetine but via 5HT 3 receptor antagonism ( 15 ). Vortioxetine has also been demonstrated to raise dopamine levels in the prefrontal cortex ( 14 ), which is thought to be owing to a 5-HT 1A agonist effect ( 16 ).…”
Section: Introductionmentioning
confidence: 99%